EFFECTS OF FEEDING BOVINE RUMEN CONTENT-BLOOD MEAL (50:50) MIXTURES ON PERFORMANCE AND SLAUGHTER CHARACTERISTICS OF GROWING RABBITS - O.O. Ojebiyi; A.S. Saliu (Journal of Animal and Plant Sciences, 2014)
The synergistic effects of combining bovine rumen content-blood meal (50:50) (BRC-BM) mixtures on the performance characteristics and nutrient digestibility of growing rabbits was investigated in a 12 week feeding experiment. The mixture replaced palm kernel cake and groundnut cake of the control at 10 and 20% levels. Thirty (30) cross-bred growing rabbits with average initial weights of 521.3-524.5 ±85.10 g were divided into three treatment groups of ten (10) rabbits each. Each rabbit served as a replicate in a complete randomized design experiment. The three groups were assigned to the three dietary treatments as T1 (control) - 0% Rumen content/ blood meal mixture (50:50), T2 (RB 10)- 10 % Rumen content/ blood meal mixture (50:50) and T3 (RB 20) -20 % Rumen content/ blood meal mixture (50:50). The final weight of rabbits on RB10 (1916g) was higher (P<0.05) compared with the control (1715g) and RB20 (1700.g) treatments. Similarly the average daily weight gain of rabbits on RB10 (16.2) was higher (P<0.05) compared with the control (11.8g) and RB20 (12.4g). The average daily feed intake of rabbits in RB10 and RB 20 (87.29g) and (85.50g) respectively was higher (P<0.05) compared to the control (82.84g). The cost per kg gain was lower (P<0.05) in the RB10 compared with control and RB20 treatments. The digestibility of nutrients was not affected (P>0.05) by the dietary treatment. The dressing percentage, relative heart and spleen weights were not affected (P>0.05) by the dietary treatments; however, liver, lungs and kidney were affected (P<0.05). The relative kidney weights of rabbits on control diet 0.43 was lower (p<0.05) than 0.49 and 0.62 for RB10 and RB20 respectively. In a similar pattern the liver weights increased (p<0.05) as the level of inclusion increases. The relative lung weights of rabbits in RB10 (0.59) and RB20 (0.60) are similar (P>0.05) but higher (p<0.05) than 0.45 of the control. Experiment concluded that bovine rumen content-blood meal mixtures (BRC-BM) can replace 10% of palm kernel cake and groundnut cake in growing rabbit diets without adverse effect on growth performance, reduce the production cost and environmental pollution and the attendant impact on climate.
Keywords: growing rabbits; bovine rumen-blood content; organ weights; final weights; digestibility